Lifelong language learning...by watching TV? - Abd Ghani, Abdul Fattah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Language learning is a lifelong journey that requires continuous effort, especially in expanding vocabulary. As adults, maintaining motivation and opportunities for growth can be challenging, but creative approaches—such as watching TV series with rich and uncommon vocabulary—can help. By paying attention to how words like “cathartic” or “expatiate” are used in context, viewers can enhance their comprehension and naturally integrate new vocabulary into their language skills beyond formal education.